2013
DOI: 10.1519/jsc.0b013e318276bb4c
|View full text |Cite
|
Sign up to set email alerts
|

Association of Weekly Strength Exercise Frequency and Academic Performance Among Students at a Large University in the United States

Abstract: The study aimed to examine (a) the association between weekly strength exercise frequency and grade point average (GPA), and (b) the demographic characteristics of weekly strength exercise frequency among undergraduate students at a large southern state university in the United States. Health behavior data (N = 1125) collected by the American College Health Association at the university in 2008 were analyzed. Analysis of variance was used to investigate weekly strength exercise frequency differences in GPA, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 29 publications
(51 reference statements)
2
35
0
7
Order By: Relevance
“…[30][31][32] The ATSs in our study participated in more PA than the general population, and based on a recent systematic review, 32 this could lead to better academic performance. Results from the review suggested that more than 50% of all associations between PA and academic achievement were positive, whereas only 1.5% were negative; the remaining 48% showed no association.…”
Section: Work-life Balancementioning
confidence: 94%
See 1 more Smart Citation
“…[30][31][32] The ATSs in our study participated in more PA than the general population, and based on a recent systematic review, 32 this could lead to better academic performance. Results from the review suggested that more than 50% of all associations between PA and academic achievement were positive, whereas only 1.5% were negative; the remaining 48% showed no association.…”
Section: Work-life Balancementioning
confidence: 94%
“…Results from the review suggested that more than 50% of all associations between PA and academic achievement were positive, whereas only 1.5% were negative; the remaining 48% showed no association. 32 Although these studies were conducted primarily in school-aged children, a recent study 31 of college students demonstrated that those students who more frequently engaged in strength-training activities had higher grade point averages. Our findings did not show a link between grade point average and engagement of PA, yet research in this area has shown promising results.…”
Section: Work-life Balancementioning
confidence: 99%
“…A potential solution for this problem of insufficient activity is the promotion of healthy behaviours via physical activity interventions on university campuses, which have been associated with increased physiological and psychological health benefits such as increases in overall fitness, reduction of stress, and improved academic performance (Freudenberg et al, 2013;Keating et al, 2013). For example, brisk walking included in daily commutes is a form of moderate-intensity aerobic physical activity that contributes to energy expenditure, which, in turn, is a valuable way to improve personal health (Warburton et al, 2006;Wener & Evans, 2007).…”
Section: University Students' Physical Activity Levels and The Value mentioning
confidence: 99%
“…For example, brisk walking included in daily commutes is a form of moderate-intensity aerobic physical activity that contributes to energy expenditure, which, in turn, is a valuable way to improve personal health (Warburton et al, 2006;Wener & Evans, 2007). This is illustrated by Tully and Cupples (2011) increased amount of walking for university students could contribute to overall increases in physical activity levels, which are associated with the promotion of good physical and mental health, as well as increases in academic performance (Besser & Dannenberg, 2005;Keating et al, 2013;MacDonald, Stokes, Cohen, Kofner, & Ridgeway, 2010).…”
Section: University Students' Physical Activity Levels and The Value mentioning
confidence: 99%
See 1 more Smart Citation